Neuro-Fuzzy Algorithm Implemented In Altera’s FPGA For Mobile Robot’s Obstacle Avoidance Mission. - Mahyuddin, Muhammad Nasiruddin; Chan, Zhi Wei; Arshad, Mohd Rizal (2009)

(untitled)
This paper presents the designed obstacle avoidance program for mobile robot that incorporates a neuro-fuzzy algorithm using Altera™ Field Programmable Gate Array (FPGA) development DE2 board.